The Mak2 MAP kinase signal transduction pathway is required for pathogenicity in Stagonospora nodorum - Solomon, P.; Waters, O.; Simmonds, J.; Cooper, R.; Oliver, Richard (Springer, 2005)
A gene encoding a mitogen-activated protein kinase (MAPK) putatively orthologous to Pmk1 from Magnaporthe grisea was cloned and characterised from the wheat glume blotch pathogen Stagonospora nodorum. Protein sequence alignments showed the cloned gene, Mak2, is closely related to homologues from other dothideomycete fungi. Expression studies revealed Mak2 is up-regulated during in vitro growth upon nitrogen starvation but is not sensitive to carbon starvation or osmotic stress. Transcript analysis in planta showed Mak2 to be expressed throughout infection and up-regulated during the sporulation phase of the infection cycle. Fungal strains harbouring a disrupted Mak2 gene were created by homologous gene recombination. The mutant strains had a severely altered phenotype in vitro with reduced growth rate and failure to sporulate. Further phenotypic analysis revealed that the mutants had near-normal levels of secreted protease activity, were not hypersensitive to osmotic stress and appeared to have melanin synthesis intact. The mak2 strains were essentially non-pathogenic to wheat leaves. No penetration structures formed and although entry was observed through stomates, the infection rarely continued. The results within this study are discussed within the context of the differences in downstream regulation of the Mak2 MAPK pathway and the cAMP signal transduction pathway in S. nodorum; and differences are compared to mak2 mutant strains in other pathogenic fungi